POLITICAL CHALLENGES IN THE EUROPEAN UNION AND INDIA FREE TRADE AND BIOTECHNOLOGY STRATEGIC PARTNERSHIP - Pangarsi, Nini Mumpuni Putri; Widayanto, Sulistyo; Indrayani, Irma (Universitas Nasional, 2024)
The 15th European Union and India Summit held in 2020 indicated that there have been over 50 years of cooperation between the two international actors with their first diplomatic relations that began in 1962. From the summit, the EU – India will form a strategic partnership to carry out collective economic recovery and overcome the global pandemic through increasing trade and biotechnology cooperation. By using qualitative methods through literature studies and a liberalism paradigm approach, the results of the analysis show that there are political challenges from both parties in implementing or following up initiatives to combine free trade and biotechnology cooperation.